Pahang food terminologies: Young generations’ understanding and usage / Khairunnisa Mohamad Abdullah ... [et al.] - Mohamad Abdullah, Khairunnisa; Ismail, Faridah Hanim; Zamzuri, Norol Hamiza; Abdul Aziz, Saidatul Afzan; Muhamad, Rosmaliza (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
This paper empirically examines the level of understanding of Pahang food names terminologies and its influence on the usage among the young Malay generation with the age range of between 18 to 30 years old. A causal research design using a quantitative through crosssectional approach was used for data collection. The results revealed that majority of the respondents have a relatively little understanding and usage of the terminologies. Relevant authorities either public or private sector should undertake actions and efforts to improve the understanding and the usage of the terminologies especially among the young generation besides preserving the Pahang foods, language and heritage at the same time.